Перші результати атмомагнітного контролю стану довкілля на прикладі міста Київ - Меньшов, О.І. (Теоретичні та прикладні аспекти геоінформатики, 2014)
Досліджено пилову фракцію як індикатор забруднення атмосферного повітря. Наведено рекогносцирувальні результати вивчення магнітної сприйнятливості зразків, що відібрані з плоских поверхонь за допомогою оригінальних пасток у різних районах м. Києва та його околиць. Точки відбору зразків розрізняються за географічною орієнтацією, техногенним навантаженням, висотою над поверхнею Землі. Исследуется пылевая фракция как индикатор загрязнения атмосферного воздуха. Демонстрируются рекогносцировочные результаты изучения магнитной восприимчивости образцов, отобранных с плоских поверхностей с помощью оригинальных ловушек в разных районах г. Киев и его окрестностей. Точки отбора образцов различаются по географической ориентации, техногенной нагрузке, высоте над поверхностью Земли. The greatest part of humanity today lives in cities and the urbanization trend in modern society will occur over the next decades. The working capacity of the population is largely determined by environmental conditions within the cities. The available ways of air pollution control are laborious and costly. Magnetic investigation of environmental pollution is the opportunity to intensify these control activities. Magnetic studies include the investigations of various objects that are able to accumulate dust particles dangerous to human health. The particles are transferred into air with magnetic minerals containing chemical compounds and elements. The selection of dust particles as an indicator of air pollution was conducted in our investigation. The initial results of magnetic susceptibility investigation for samples selected from flat surfaces using the original traps in different districts of Kyiv and its environs are demonstrated. Sampling points are differentiated by geographical orientation, technogenic load, height above Earth’s surface.